Calculation of Positive and Negative Parity Energy Levels Using IVBM for Some Molybdenum Isotopes and Determination of Their Properties - Souad M. Bogrin; Karima M. Musa; Sadiq M. El-Kadi (African Journal of Advanced Pure and Applied Sciences, 2024)
The calculations of the excited positive and negative parity bands of the isotopes were achieved by using the Interacting Vector Boson Model (IVBM) extension. The bands investigated in the model are extended to very high angular momenta as a result of their consideration as Octopole bands concerning simplistic classiﬁcation of the basis states. The characteristic of collective behavior by using R ratio, and E-GOS for the isotopes have been determined. Furthermore the ∆I = 1 staggering as a function of the angular momentum (I) has been examined.